Optimalisasi Waktu dan Biaya Pada Proyek Gedung Pertanahan Nasional Kota Blitar Dengan Metode Critical Path Method (CPM) - Bobby Damara; Rasio Hepiyanto (Kadiri University, 2021)
Cost and time control is a key aspect of construction management. In its planning, both aspects need to be done appropriately to get optimal results. Building construction cannot be separated from various obstacles that cause delays in work until the cost of repairs. This research aims to optimize the cost and time in the Blitar National Land building by using the CPM (Critical Path Method) Method. The method is applied by using Microsoft project software to find out the critical paths are located in each division of the work by creating network diagrams and delayed scenarios. The results of the study obtained critical pathways occurred inactivity (A, B, C, D, E, G, H, I, L and M). From the critical path, an increase in the number of workers and the duration of work (overtime) to prevent delays. The prevention takes a fee of Rp 290,617,244 with the duration of work (Activity B) requires 15 additional workers, 8 hours of overtime. Â Â (Activity C) it takes 3 additional workers and 1hour additional overtime time and on (Activity H) requires 6 additional workers with overtime for 1 hour.